دا ا ت ا ا ا داة ا دة ا إدارة ت !"# ى% - التجاني, عاصم (جامعة المسيلة, 2017)
This study aims at investigating the application of the requirements of total quality management in the university college for girls as a tool for achieving competitive advantage as well as identify the relation between these requirement and competitive advantage. the requirement are measured in sex points : the administration commitment to quality ; training of personnel ; personnel participation; social responsibility ;continual improvement of educational process, and focusing on students .The study sample consists of (60) of the college staff including member of teaching staff .The instrument of data collection is that of the questionnaire. The study shows that there vis a statistically signification correlation between the requirements of the management of total quality and competitive advantage in the university college for girls as indicated by the results of the multi-faceted analysis .the six independent variables, included in the model, all account for (69%)of the changes occurring in the competitive advantage in Sudan university – for girls. The study found that the Sudan's university college for girls ,and due to its concern with the requirement of the management of total quality gained competitive advantages from its available resources of programs and academic specializations that suit the woman's nature and the requirement of labor market in the private and public sectors alike ,despite the results that show that the ph-d holder constitute only (13.3%)which can be attributed to the college reliance on part-time staff from other colleges and universities instead of appointing staff in the college
Keywords: total quality management. Competitive advantage .